2015
DOI: 10.1158/1541-7786.mcr-14-0292-t
|View full text |Cite
|
Sign up to set email alerts
|

WHSC1 Promotes Oncogenesis through Regulation of NIMA-Related Kinase-7 in Squamous Cell Carcinoma of the Head and Neck

Abstract: Squamous cell carcinoma of the head and neck (SCCHN) is a relatively common malignancy with suboptimal long-term prognosis, thus new treatment strategies are urgently needed. Over the last decade, histone methyltransferases (HMT) have been recognized as promising targets for cancer therapy, but their mechanism of action in most solid tumors, including SCCHN, remains to be elucidated. This study investigated the role of Wolf-Hirschhorn syndrome candidate 1 (WHSC1), an NSD family HMT, in SCCHN. Immunohistochemic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 58 publications
0
76
0
1
Order By: Relevance
“…The oncogenic role of WHSC1 was first reported in multiple myeloma, in which the (4;14)(p16;q32) translocation results in WHSC1 overexpression (29)(30)(31). WHSC1 is also frequently overexpressed in solid tumors such as oligodendroglioma, breast, prostate, and head and neck cancers (32)(33)(34). Cell culture studies indicated that WHSC1 modulates NIMA-related kinase-7 (NEK7), Twist family bHLH transcription factor 1 (TWIST1), and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κΒ) to promote tumorigenesis (34)(35)(36).…”
Section: Whsc1 Promotes the Metastasis Of Pca Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogenic role of WHSC1 was first reported in multiple myeloma, in which the (4;14)(p16;q32) translocation results in WHSC1 overexpression (29)(30)(31). WHSC1 is also frequently overexpressed in solid tumors such as oligodendroglioma, breast, prostate, and head and neck cancers (32)(33)(34). Cell culture studies indicated that WHSC1 modulates NIMA-related kinase-7 (NEK7), Twist family bHLH transcription factor 1 (TWIST1), and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κΒ) to promote tumorigenesis (34)(35)(36).…”
Section: Whsc1 Promotes the Metastasis Of Pca Cellsmentioning
confidence: 99%
“…WHSC1 is also frequently overexpressed in solid tumors such as oligodendroglioma, breast, prostate, and head and neck cancers (32)(33)(34). Cell culture studies indicated that WHSC1 modulates NIMA-related kinase-7 (NEK7), Twist family bHLH transcription factor 1 (TWIST1), and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κΒ) to promote tumorigenesis (34)(35)(36). Nevertheless, the genetic characterization of WHSC1 to determine its role in PCa metastasis and the signaling coordinated by WHSC1 remain undefined.…”
Section: Whsc1 Promotes the Metastasis Of Pca Cellsmentioning
confidence: 99%
“…Given that WHSC1L1 is recurrently amplified in SCCHN and that few studies have explored the role of PKMTs in SCCHN [8], we aimed to evaluate its potential function as an oncogenic force in this disease, and to elucidate relevant mechanisms of its oncogenic activity. In this study, we show that WHSC1L1 is significantly overexpressed in patients with SCCHN, its knockdown causes cell-cycle arrest and decrease in global H3K36 dimethylation levels, and that it promotes the coordinated transcription of a number of cell cycle genes, including CDK2 and CDC6, which are critical for the G1/S transition.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, NSD2 has been reported to be upregulated in a number of solid cancers such as squamous cell carcinoma of the head and neck7, endometrial cancer8, lung cancer910, neuroblastoma11, bladder and colon cancer910, hepatocellular carcinoma12, ovarian carcinoma13 and prostate cancer14. Overexpression in solid tumors appears to occur in the absence of genetic alterations.…”
mentioning
confidence: 99%